Acoustic backscatter by suspended cohesive sediments: Field observations, Seine Estuary, France. (15th February 2017) - Sahin, Cihan; Verney, Romaric; Sheremet, Alexandru; Voulgaris, George
Abstract: Observations of suspended sediment size and concentration, flow and acoustic backscatter intensity collected on the Seine Estuary (France) are used to study the acoustic response in cohesive-sediment dominated environments. Estimates of suspended sediment concentration based on optical backscatter sensors and water samples are used to calibrate the acoustic backscatter intensity. The vertical structure of suspended sediment concentration is then estimated from acoustic backscatter information. To our knowledge, this is the first field application of the recently proposed model of acoustic scattering by flocculating suspensions based on the variation of particle density (floc-scattering model). The estimates of sediment concentration reproduce well the observations under different tidal (neap/spring) conditions, confirming the applicability of the new model in the field when detailed particle size measurements are available. When particle size measurements are not available, using estimated floc sizes based on the turbulence intensities may provide reasonable SSC profiles. During spring tide events (associated with strong currents, small flocs and large concentrations), the performances of the new floc-scattering model and the previous models given for solid particle-scattering are comparable. The floc-scattering model increases the quality of the SSC estimates especially during low-energy conditions characterized with larger flocs. Abstract : Highlights: First field application of the recent model of acoustic scattering by mud flocs. Applicability of the new model is confirmed with detailed floc size measurements. Using floc size estimates from turbulence intensities may provide reasonable SSCs. Floc-scattering model increases the quality of results during low-energy conditions.